Altered topological organization of resting-state functional networks in children with infantile spasms - Wang, Ya; Li, Yongxin; Yang, Lin; Huang, Wenhua (Frontiers in Neuroscience, 2022)
Covering neuroimaging evidence has demonstrated that epileptic symptoms are associated with disrupted topological architecture of brain network. Infantile spasms (IS) as an age-specific epileptic encephalopathy also showed abnormal structural or functional connectivity in specific brain regions or specific network. However, little is known about the topological alterations of whole-brain functional networks in IS patients. To fill this gap, we used graph theoretical analysis to investigate the topological properties (whole-brain small-world property and modular interaction) in 17 IS patients and 34 age- and gender-matched healthy controls. The functional networks in both groups showed efficient small-world architecture over the sparsity range from 0.05 to 0.4. While the IS patients showed abnormal global properties characterized by significantly decreased normalized clustering coefficient, normalized path length, small-worldness, local efficiency, and significantly increased global efficiency, implying a shift towards randomized network. Modular analysis revealed decreased intra-modular connectivity within default mode network (DMN), fronto-parietal network, but increased inter-modular connectivity between the cingulo-opercular network and occipital network. Moreover, the decreased intra-modular connectivity in DMN was significantly negatively correlated with seizure frequency. The internetwork connectivity between the cingulo-opercular and occipital network also showed significant correlation with epilepsy frequency. Together, the current study revealed the disrupted topological organization of whole-brain functional network, which greatly advances our understanding of neuronal architecture in IS and may contribute to predict the prognosis of IS as disease biomarkers.